Reciting QS. Al-Ra`d and QS. Yāsīn in Phenomena of Sakarāt al-Maut in Sumenep, Madura - Muttaqin, Khairul; Afifullah, Afifullah; Nurhayati, Sri (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2022)
This article discusses the phenomenon of the reciting QS. Yāsīn and QS. al-Ra’d to people who experience critical conditions such as for someone who becomes the door of death (Sakarat al-Maut) which is widely done in Sumenep Madura Regency. Sumenep people assume that reciting surah al-Ra’d and Surah Yasin to people who experience door of death (Sakarat al-Maut) can speed up the process or provide healing, however, in that aspect of the meaning of the two Surah is not related to the phenomenon of door of death (Sakarat al-Maut). This shows that the Sumenep people in this tradition have a different reception from the literal meaning of these two surahs. Therefore, this study aims to see how the Sumenep people’s understanding of surah Yāsīn and surah al-Ra’d and how the structure forming the phenomenon of the use of the two Surahs in the phenomenon door of death (Sakarat al-Maut). This article is qualitative type research with the use of field research (field research) or field studies as a research method. The approach used as an analytical method is Edmund Husserl’s phenomenological approach. This approach looks at a phenomenon in the absence of the assumptions that accompany it during the process of observation and collection of field data. The results of this study show that in some areas in Sumenep Regency are commonly recited surah Yāsīn or surah al-Ra’d or surah Muhammad or surah Yāsīn with surah al-Ra’d, or surah Yāsīn with al-Qiyamah, or surah Yāsīn and al-Taubah or surah Yāsīn and al-Kahfi to people who experience door of death (Sakarat al-Maut). The basis of the reading is the Hadith of the Prophet (peace be upon him) and the explanation of the salaf books.